Psychomotoric therapy in patients with dementia - Jitka Suchá; Iva Holmerová (Palacký University Olomouc, 2016)
Background: Dementia syndrome is a significant psychosocial and public health problem with important societal impact. It is important for us to learn more about methods of dementia management. Objective: To discuss principles and basic measures of psychomotor therapy in patients with dementia as well as the implementation of movement therapy and the lifestyle of patients with dementia. Methods: This research presents experience with psychomotor therapy of patients with dementia from the Centre of Gerontology - a day care unit for patients with dementia. Results: Physical activity is an important component in the management of dementia. Implementation of movement should be based on individual needs of persons with dementia and on their abilities. Individual programs and regular training have been pointed out as important principles in care and implementation of physical activity. Other physical activities could be included in the daily programme as well such as different sports and other movements if appropriate to the status of patients and advancement of the dementia syndrome. Conclusion: Regular structured physical activities should be a regular part of the daily programme in the care of patients with dementia.